Investigation on split-ring resonators based on different substrates and dimensions operating at terahertz frequency / Muhammad Zahiruddin Mohd Zahari - Mohd Zahari, Muhammad Zahiruddin (2007)
Radiation in the THz band, 0.3 to 30 THz, presents difficulties to workers in the engineering and physics field; because the band is positioned between microwave and optical frequencies. Recent developments in terahertz sources include compacted electron beam systems, optical mixing techniques, and multiplication of microwave frequencies. Despite significant advances in THz science, however, few source technologies are mobile or suited for field deployment. Strategies in source development have approached generation from either end of the THz spectrum, from up-conversion of high-frequency microwave to down-conversion of optical frequencies. In order to operate at THz frequencies, a composite material may be engineered to manifest optical effects for a particular range of frequencies. The term metamaterial encompasses materials with subwavelength structures whose aggregate interacts in a macroscopic manner with radiation of a specific wavelength. The split ring resonator (SRRs) geometry investigated in this project falls under this heading. Metamaterials that serve as THz active elements are well established and promise to yield new technologies that are smaller, cheaper, and more efficient than previous methods. This project report presents the investigation on the response of split-ring resonators (SRRs) with the operating or resonant frequency approximately at ITHz. Different substrates and dimensions of the rings are investigated to observe the response of the SRRs at the operating frequency. The main parameters concern for this project is the voltage standing wave ratio (VSWR), return loss (Su) and the resonant frequency. The SRRs is simulated using CST Microwave Studio 2006 to obtain the response used for the investigation.